Immune competence and disease resistance in broiler chicks as influenced by genotypes and dietary energy levels - Praharaj, N K; Sridevi, B; Reddy, M R; Rao, S V Rama; Panda, A K (The Indian Journal of Animal Sciences, 2012)
An experiment was conducted to measure immune competence and disease resistance in chicks from 4 different male broiler parent lines maintained on 3 diets (2 500, 2 700 and 2 900 kcal ME / kg of feed, respectively) fed ad lib. through 1 to 35 days of age. On 36 day of age, chicks from 2 replicates (10 birds) in each genotype under each diet were injected with sheep red blood cells (SRBC), another 2 replicates (10 birds) with E. coli (serotype 02) culture. The response to SRBC and E. coli inoculation was measured 5 days post inoculation. On 41 day of age, the chicks of the final replicate were injected intradermally in wattle with phytohaemagglutinin-M (PHA-M) and the thickness was measured 12 and 24 hr post inoculation. The antibody titres were significant for genotypes and for diets. There were significant differences among genotypes for E. coli score and thickness of wattle. From this it is evident that genotypes and energy content in diet influence immune competence and disease resistance.